2018
DOI: 10.1111/bph.14449
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin protects against experimental colonic inflammation in mice

Abstract: Calprotectin exerted protective effects in experimental colitis when given by the intrarectal route, by actions that appear to involve effects on the epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 54 publications
3
9
0
1
Order By: Relevance
“…Moreover, MMI-0100 suppressed activation of CD11b+ and F4/80 positive cell induced by DSS, and dramatically decreased the expression level of a series of pro-inflammatory cytokines such as TNF-α, IL-6, IL-1β, TGF- β, IFN-γ, IL-17A, COX-2 and iNOS. Previous articles have reported protective roles of calprotectin and lipocalin 2 against colitis [27,28]. Our data indicated that MMI-0100 significantly increased the expression level of calprotectin B and lipocalin 2, and down-regulated in the increase of CRP induced by DSS.…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, MMI-0100 suppressed activation of CD11b+ and F4/80 positive cell induced by DSS, and dramatically decreased the expression level of a series of pro-inflammatory cytokines such as TNF-α, IL-6, IL-1β, TGF- β, IFN-γ, IL-17A, COX-2 and iNOS. Previous articles have reported protective roles of calprotectin and lipocalin 2 against colitis [27,28]. Our data indicated that MMI-0100 significantly increased the expression level of calprotectin B and lipocalin 2, and down-regulated in the increase of CRP induced by DSS.…”
Section: Discussionsupporting
confidence: 66%
“…RAGE activity has already been linked to active IBD [15] as well as other inflammatory diseases including diabetes, Alzheimer’s, airway inflammation, cancer and haemorrhagic shock [16]. Additionally, several RAGE ligands have been identified as associated with the inflammation in IBD, including calprotectin, EN-RAGE and HMGB1 [1719]. Thus, our data from the mouse model shows a clear link to known pathology in IBD.…”
Section: Discussionsupporting
confidence: 54%
“…Fecal calprotectin changes were seen in our colitic mice fed differing iron diets, being greater in those animals consuming an iron-deficient diet in the acute colitis model, and with the iron supplemented diet in the chronic colitis model, most likely reflecting an enhanced protective response against inflammation-induced damage [ 33 ].…”
Section: Discussionmentioning
confidence: 99%